Application of different methods for determining intensity-duration-frequency curves in Belterra in the state of Pará, Brazil (Research, Society and Development, 2020)
Due to the continental dimension of the state of Pará, associated with the absence of more accurate rainfall data, a study was carried out on them in order to obtain a ratio of rainfall intensity, duration and frequency (IDF) for the municipality of Belterra, through the application of 3 methods, the Normal IDF curve, Bell's method and the Gumbel Disaggregation method. The Belterra rainfall station, available from the National Meteorological Institute - INMET, with a 30-year historical series of data, was used as a basis for this. Only the maximum rains for the construction of the IDF curves were analyzed, with duration times of 5, 10, 15, 20, 25, 30, 60, 360, 480, 600 and 720 min and return periods of 2, 10 and 25 years. The objective of the research was to develop the 3 methods and later compare them, in order to assist in hydrological studies and for the design of structures that use this methodology. The values of rain intensities were compared with each other, where the Bell method, for the return times of 10, 15 and 25 years, presented higher values of Rain Intensities, however, when analyzing for the period of 2 years, the method that obtained an IDF with higher intensities was the Normal method. In all 4 periods analyzed, the disaggregation method (Gumbel) presented lower values for the respective rainfall duration times, which does not make its method unfeasible, since it also depends on what purpose it will be used for.